Dynamics of Tidal and Residual Currents Based on Coastal Acoustic Tomography Assimilated Data Obtained in Jiaozhou Bay, China. Issue 6 (3rd June 2021) - Zhu, Ze‐Nan; Zhu, Xiao‐Hua; Zhang, Chuanzheng; Chen, Minmo; Wang, Min; Dong, Menghong; Liu, Wenhu; Zheng, Hua; Kaneko, Arata
Abstract: To investigate the dynamics of tidal and residual currents in a shallow bay with narrow bay mouth and large tidal flat area, this study conducted three sets of coastal acoustic tomography (CAT) observations at 13 stations in deep area of Jiaozhou Bay (JZB), China, from December 6–18, 2015. Thereafter, travel time difference data observed via CAT were assimilated into a barotropic tidal model to realize an extrapolated study in tidal flats. The root mean square difference was 6.5 cm/s between assimilation and acoustic Doppler current profile data. Harmonic analyses indicated that the semidiurnal tide (M2) was predominant; however, relatively large nonlinear tidal currents (M4 and M6) were also found. Moreover, the spatial mean amplitudes of M2, M4, and M6 were 0.35 (excluding the tidal flat), 0.09, and 0.04 m/s, respectively. Dynamic analyses showed that continuity and advection terms were the main contributors to M4 in the bay mouth, whereas M4 in the tidal flats was generated by continuity and friction terms. Furthermore, bottom friction was the primary contributor to M6. In addition, residual currents with multi‐vortex structures appeared near the bay mouth, the maximum speed reached 0.60 m/s, and advection, continuity, and bottom friction contributed more to the generation of residual current eddies. Horizontal pressure gradient of residual elevation and advection of tidal and residual currents were the dominant factors maintaining the residual current near the bay mouth. The generation mechanisms of M4 and M6 were first discussed based on the assimilation of the current field data in JZB. Plain Language Summary: Nonlinear tidal currents M4 and M6, which are principle overtides in the regions where M2 is dominant, have considerable impact on mass transport and marine ecosystems. Observations of M4 and M6 can help us understand physical oceanography processes in coastal regions. However, the current generation mechanisms are complicated in different coastal regions. Furthermore, nonlinear factors, such as advection terms, are difficult to examine by traditional observational technics. Coastal acoustic tomography (CAT) is useful to map tidal current fields over large areas in coastal regions. Thus, it is suitable for analyzing the dynamic mechanisms of M4 and M6. We obtained current fields with high accuracy and spatial resolution in Jiaozhou Bay, China, by assimilating CAT observational data into a barotropic ocean model. Using them, we demonstrate that continuity and advection terms are the main contributors to M4 in the bay mouth, whereas M4 in the tidal flats was generated by continuity and friction terms. Bottom friction is the primary contributor to M6. Our study serves as a good supplement to the previous studies on nonlinear tides in Jiaozhou Bay. Furthermore, CAT can be considered to obtain high accuracy current data and for further dynamic studies. Key Points: Thirteen coastal acoustic tomography stations were deployed to obtain current field data in Jiaozhou Bay, China Tidal and residual currents were obtained by data assimilation based on coastal acoustic tomography observations Generation mechanisms for nonlinear and residual tidal currents in Jiaozhou Bay were demonstrated